(untitled) (Papeles, 2024)
This work addresses the personal and academic trajectories of researchers in the province of Jujuy, based on biographical interviews. This qualitative study with a case study seeks to understand the dynamics of training, research and scientific production in a specific regional context. The information obtained is examined in light of Latin American theories and studies on higher education, academic trajectories and scientific production. The analysis reveals a complex panorama where personal, institutional and structural factors converge that shape the development of a scientific career. In conclusion, valuable perspectives are offered on the modalities of training, production and circulation of knowledge in recent decades in northwest Argentina.